Experimental and Finite Element Studies on Free Vibration of Areca Leaf Sheath Reinforced Polymer Composites - R. Ashok; Chikkol Srinivasa; B. Basavaraju (Mechanics of Advanced Composite Structures)
The present work deals with the experimental and finite element free vibration studies on areca leaf sheath reinforced polymer composites. In this study fundamental frequencies are obtained for five boundary conditions numerically (such as CFFF, CFCF, SSSS, CSCS and CCCC) and only for 2 boundary conditions (CFFF and CFCF) experimentally. The natural frequencies were determined using the CQUAD8 finite element of MSC/NASTRAN and a comparison made between the experimental values and the finite element solution. The effects of age of areca palm, number of layers, type of surface modification, and boundary conditions on the natural frequencies of composites were studied. The experimental values of the first, second, and third natural frequencies agree with those of the finite element solution in the case of areca leaf sheath reinforced composites under CFFF and CFCF boundary conditions. The natural frequency values increased with an increase in the number of layers, age of areca palm, and alkali percentage from 5 to 15%. Among the different boundary conditions considered, composites with the CCCC boundary condition have exhibited higher values of natural frequencies than other boundary conditions under finite element solutions.